Simple.ology - "Joyner, Mark" (New Jersey, 2007)
Success is simple, and scientifically reproducible, if you know the 5 Laws Simpleology proves that success and happiness are easier to achieve than most people think they are. In fact, people can almost guarantee their own success simply by following a few simple rules. These "5 Laws of Simpleology" arena t new; theya ve been around forever. Throughout history, these 5 laws have helped the worlda s greatest minds amass fortunes and forge new paths. But until now, no one has committed them to paper in so simple and straightforward a style as Mark Joyner has here. Applicable to any challenge or goal and irrefutably commonsense, these 5 laws form the basis for almost any successful person or endeavor. Simpleology explains the 5 laws in detail and shows readers how to apply them to every aspect of their lives. Mark Joyner (Auckland, New Zealand) is a leading authority on Internet marketing. The former CEO of Aesop Marketing Corp., he is the author of four previous books, including The Irresistible Offer (0--471--73894--8) and The Great Formula (0--471--77823--0), both from Wiley.
Keywords: Self - actualization (Psychology)